2014
DOI: 10.3768/rtipress.2014.rb.0007.1405
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease of unknown etiology in Sri Lanka: Quest for understanding and global implications

Abstract: CKDu: A Growing Global Concern• CKDu patients are most often men ages 30 to 60, their most productive working years• CKDu symptoms appear in the late stages of the disease• Causes for CKDu are unknown but are multifaceted• Risk factors include environment, agricultural work and farming practices, diet and nutrition, and geneticsAn important global public health concern is unfolding around chronic kidney disease of unknown etiology (CKDu). CKDu presents as kidney disease in patients who do not exhibit common ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 8 publications
(13 reference statements)
0
44
0
Order By: Relevance
“…In our review, only two studies from Sri Lanka and two studies from Central America reported a significant association between agrochemical use and CKDu. Agrochemical use was not reported in studies from other regions, suggesting the possibility of a distinct etiology for CKD in agricultural communities in CKDu-endemic regions (6,(11)(12)(13)(14). These findings may reflect variation in the regional exposures being studied as well as difficulties in defining and quantifying agrochemical exposure, but they also highlight the need for more conclusive epidemiologic studies examining causation, particularly in agricultural communities in CKDu-endemic regions.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In our review, only two studies from Sri Lanka and two studies from Central America reported a significant association between agrochemical use and CKDu. Agrochemical use was not reported in studies from other regions, suggesting the possibility of a distinct etiology for CKD in agricultural communities in CKDu-endemic regions (6,(11)(12)(13)(14). These findings may reflect variation in the regional exposures being studied as well as difficulties in defining and quantifying agrochemical exposure, but they also highlight the need for more conclusive epidemiologic studies examining causation, particularly in agricultural communities in CKDu-endemic regions.…”
Section: Discussionmentioning
confidence: 56%
“…Subsequently, this disease pattern, which was similar to that of Balkan Endemic Nephropathy (9), was reported in other countries, including Nicaragua, Costa Rica, and Sri Lanka (6,(10)(11)(12), and its prevalence is now as high as 16% in some of these areas (13). In El Salvador, ESRD that is largely attributable to CKDu has become the leading cause of hospital deaths (8), and in Sri Lanka, nearly 4% of the national health care budget is now spent on treating CKDu (14,15). As such, it has become a public health priority and the focus of many World Health Organization-sponsored epidemiologic studies (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Cases of this disease predominate in the Medawachchiya, Wilgamuwa, Nikawewa, and Girandurukotte regions of the dry zone. Studies have shown the highest prevalence of CKDu among 30-60 year old men engaged in chena or rice farming, and estimate a total of 20,000 (approximately 0.8% population) affected in the North Central Province [8, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Reports from Sri Lanka and India indicate that CKDnT is also a problem in these nations. [14][15][16] There is anecdotal evidence that the problem may even exist in the migrant labor community in Western US [JG -personal communication]. Possibly, we will find CKDnT wherever we look carefully.…”
mentioning
confidence: 99%
“…Finally, research to identify how epidemics of CKDnT in other parts of the world (e.g. Sri Lanka, India, South America) [14][15][16][17] correspond to the epidemic in Mesoamerica, is getting under way. There is much left to be done but little time for so many current sufferers of CKDnT as well as those continuing at risk of developing CKDnT.…”
mentioning
confidence: 99%